Ideologi Islam Reformis dalam Tafsir - Muhammad Ihsan; Ishmatul Karimah Syam (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to explain the interpretation of the reformist era, in terms of ideology, influence, commentators who existed at that time, and criticisms of their commentators on traditional Islam. This study uses qualitative methods with descriptive analysis sourced from literature studies. This paper concludes that reformists took place in the 20th century due to European expansion. The presence of this ideology also affects science, especially in the field of interpretation. Tafsir in this century was heavily influenced by the thoughts of Egyptian reformers such as Muhammad Abduh and others. Its development has progressed rapidly, such as various new styles and methods coming afterward. The commentators are Oemar Bakri, Buya Hamka, KH. Bisri Musthofa, Mahmud Yunus, and Quraish Shihab, the reformists, also criticized the traditionalists who were considered too blind to taqlid towards the ulama. Also, their thoughts which are still shackled by customs, have become sharp criticisms of the reformists against traditionalists. This reformist or renewal is considered a breath of fresh air for Muslims to be more modernist, technological, and not lagging behind western progress.